2018
DOI: 10.1371/journal.pone.0203278
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in factors associated with prehypertension and hypertension in Nepal: A nationwide survey

Abstract: BackgroundNepal has one of the highest prevalence of hypertension in South Asia. However, no national studies have examined the gender differences in the determinants of prehypertension and hypertension in the country to inform targeted interventions. This study aimed to investigate gender differences in factors associated with prehypertension and hypertension in Nepal using the 2016 Nepal Demographic and Health Survey (NDHS).MethodsSociodemographic, behavioural, anthropometric and health status data and infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 58 publications
6
31
1
1
Order By: Relevance
“…Several studies have reported higher risks of hypertension among people who are older in age, male, urban dwellers, have higher education level, regularly consume tobacco and/or alcohol, or are overweight. 6 8 28 29 We found that patients aged ≥65 years and who were overweight/obese were at lower risk of remaining undiagnosed from hypertension. Our findings depicted a greater proportion of undiagnosed hypertensive patients among those who were young and those with lower BMI.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Several studies have reported higher risks of hypertension among people who are older in age, male, urban dwellers, have higher education level, regularly consume tobacco and/or alcohol, or are overweight. 6 8 28 29 We found that patients aged ≥65 years and who were overweight/obese were at lower risk of remaining undiagnosed from hypertension. Our findings depicted a greater proportion of undiagnosed hypertensive patients among those who were young and those with lower BMI.…”
Section: Discussionmentioning
confidence: 78%
“…Similar to risk factors of hypertension, undiagnosed hypertension was also more prevalent among males and tobacco users. 6 29 The higher rate of undiagnosed hypertension among males might be due to their lack of awareness and lower treatment rates than females. 32 Smoking, a main source of using tobacco, is well recognised to be associated with an increased risk of hypertension in many settings, including Nepal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Regitz-Zagrosek’s report, hypertension is more common in women than men in the elderly population 9. However, one study conducted in Nepal showed that prehypertension and hypertension occurred more frequently in males than famales 10…”
Section: Introductionmentioning
confidence: 99%